Otonomi Kerajaan Denpasar dalam Perspektif Sejarah: Diplomasi, Perjuangan dan Kontribusinya Bagi Bangunan Negara-Bangsa - Sancaya, I Dewa Gede Windhu; Ardhana, I Ketut (Humanis, 2024)
Bali has unique and distinctive cultural customs that have a societal and cultural character that has been dominantly influenced by Hinduism. One proof of the influence of Hindu culture originating from India was the concept of a kingdom where the king was the ruler in regulating people's lives. Even though in the modern era, Bali has become a part of the Unitary State of the Republic of Indonesia, this does not mean that the traditional system that existed before has disappeared but rather that it can become part of the formation of social and cultural capital in the context of the nation-state building in Indonesia. The kingdom of Denpasar, previously called the kingdom of Badung as well was a cultural entity which played an significant role not only in the past, but also still be seen in the modern Bali era. It is not surprising to see that the existence of this kingdom cannot be separated from the understanding of the existence of autonomy, diplomacy and the struggles and its contribution that has been carried out from the past until now. There are some significant questions that will be addresed in this paper firstly: What and how did the kingdom or Puri Denpasar exist in the dynamics of society and culture in Bali in particular and in Indonesia in general? Secondly: how did collective memory develop so that Puri Denpasar had its authority as the diplomacy and struggle carried out to contribute to the nation-state building? Thirdly: what the meaning of kingdom in the modern Bali era particularly in the context of socio and cultural aspects so that these social and cultural values can be maintained regarding its existence from the past until now within the framework of the Unitary State of the Republic of Indonesia? These are some significant questions that will be discussed in this study in an effort to have a better understanding about the role of the kingdom or Puri Denpasar in socio-cultural, economic and political aspects so that Puri Denpasar can maintain its existence until now in the context of nation-state building in the modern Indonesian state.